The Social Media and CSR Effects on Loyalty Towards Banking Services - Alsharari, Abdullah; Toukabri, Maher; Shili, Aicha (Journal of Ecohumanism, 2024)
This study explores the impact of Corporate Social Responsibility (CSR) communication via social media on shaping customer perceptions of bank reputation. By using a questionnaire to collect data from bank customers, this research develops a theoretical model to test the proposed hypotheses. A quantitative approach, with data analysis conducted using SPSS and AMOS software, will be employed to evaluate the relationships between CSR communication and customer perceptions of bank reputation. This research aims to provide valuable insights for the banking sector, particularly in emerging markets, highlighting the importance of CSR communication through social media in enhancing customer perceptions and strengthening brand reputation. The findings will assist bank managers in crafting more effective CSR strategies, fostering stronger customer loyalty, and ultimately improving business performance in an increasingly competitive and digital landscape.